Malaysian business reporting system: challenges of its implementation / Noor Amirah Abdul Rahim, Saflina Azis and Mustafa Kamal Mat - Abdul Rahim, Noor Amirah; Azis, Saflina; Mat, Mustafa Kamal (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The implementation of the Malaysian Business Reporting System (MBRS) enhances financial reporting by making data validation more efficient and minimizing human errors. The standardized submission formats also ensure consistency across companies, making comparisons easier. Moreover, MBRS supports companies in meeting regulatory compliance more effectively, thereby reducing the risk of penalties and fostering a positive relationship with regulators. However, the enforcement of MBRS has brought significant changes to corporate reporting practices in Malaysia, creating both opportunities and challenges.